Interviewing Isabel Serrano Pintado (Journal of Parents and Teachers, 2014)
In this interview, the professor and researcher in the field of children from the University of Salamanca exposes her point of view on aggressiveness, the role of the family and the school to address this issue, and presents her book "The Aggressive Child."
Keywords: Interview; aggressiveness; "The Aggressive Child".